A biomedical multifunctional coating and preparation method thereof

Through sandblasting treatment, the composite film structure is deposited with magnetron sputtering technology, which solves the problem of insufficient bone integration ability and antibacterial performance of biomedical materials, and significantly improves the biocompatibility and implantation success rate of the material.

CN119615094BActive Publication Date: 2025-04-11CHENGDU KENINGDA MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510163522.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-11
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

Existing biomedical materials such as polyether etherketone (PEEK) are bioinergenic on the surface, cell adhesion and protein absorption, resulting in poor osseous integration capabilities, increasing postoperative recovery time and possibly causing bacterial infections, resulting in implantation failure.

Method used

Sand blasting is used to form the micro-nano structure on the surface of medical materials, and the Ti transition layer is deposited through magnetron sputtering technology, alternately deposited Ta and Ti functional layers, and finally deposited Ta and Cu layers to form a composite film layer structure to enhance the biocompatibility and antibacterial properties of the material.

Benefits of technology

It improves the bone integration capability and implant success rate of medical materials, enhances the binding strength with the implanted materials, and effectively prevents bacterial infection around the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615094B_ABST
    Figure CN119615094B_ABST
Patent Text Reader

Abstract

The present application relates to the field of biomaterials, and specifically discloses a biomedical multifunctional coating and a preparation method thereof. The preparation method comprises: performing plasma treatment on the medical material after sandblasting, and then depositing a Ti transition layer; then continuing to perform magnetron sputtering coating on the transition layer surface of the medical material, alternately depositing Ta layers and Ti layers, and forming a ‑(Ta‑Ti) n -functional layer, where n=1~3; finally, a Ta layer and a Cu layer are deposited on the surface of the functional layer of the medical material. The multifunctional coating provided by the present invention, on the one hand, the Ti transition layer can form a strong bond with the medical material with a micro-nano structure on the surface, thereby improving the bonding strength of Ta; the functional layer of Ta and Ti alternating can reduce the stress of the coating and improve the bonding strength of the coating as a whole. On the other hand, this coating structure can also retain the advantages of Ta, improve the bone integration ability of the medical material, and at the same time resist infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biomaterials, and more specifically, to a biomedical multifunctional coating and a preparation method thereof. Background Art

[0002] Polyetheretherketone (PEEK) is popular in the biomedical field due to its modulus comparable to human cortical bone, radiolucency, high temperature durability, good sterilization, excellent chemical and biodegradability resistance, and excellent fatigue performance. However, due to its biological inertness, low cell adhesion and protein absorption capacity on the surface, it has poor bone integration ability, which can prolong postoperative recovery time and even cause bacterial infection leading to implant failure.

[0003] In order to solve the above problems, existing technicians use medical tantalum metal as coating material. Its main advantages are that medical tantalum metal has good biocompatibility and can promote bone integration. At the same time, tantalum has good wear resistance and corrosion resistance. However, in practical applications, due to the low bonding strength between polymer and metal coating, excessive residual stress of single-layer coating, etc., the coating has the risk of rupture; at the same time, tantalum coating still cannot overcome the problem of bacterial infection around implants.

[0004] It can be seen that there is an urgent need for a multifunctional coating that has both biocompatibility and antibacterial properties and high bonding strength with implant materials. Summary of the invention

[0005] In order to solve the above problems, the present application provides a biomedical multifunctional coating and a preparation method thereof.

[0006] The present application adopts the following technical solutions: In the first aspect, the present application provides a method for preparing a biomedical multifunctional coating, which comprises:

[0007] (1) Sandblasting the medical material to obtain a medical material with a surface micro-nano structure;

[0008] (2) A titanium target, a tantalum target, and a copper target are respectively mounted on three targets in a magnetron sputtering apparatus, and a medical material is placed in the magnetron sputtering apparatus. After evacuation, argon gas is filled in, and the medical material is subjected to plasma treatment, and the surface of the medical material is bombarded with argon ions;

[0009] (3) Performing magnetron sputtering coating on the surface of the medical material after plasma treatment to deposit a Ti transition layer;

[0010] (4) Continue to perform magnetron sputtering coating on the transition layer surface of the medical material, alternately depositing Ta layers and Ti layers to form - (Ta-Ti) n -functional layer, where n=1~3;

[0011] (5) A Ta layer is deposited on the surface of the functional layer of the medical material, and then a Cu layer is deposited on the surface of the Ta layer, and finally -Ti-(Ta-Ti) is formed on the surface of the medical material. n -Ta-Cu composite film structure.

[0012] Furthermore, the above-mentioned medical material includes any one of PEEK material, titanium alloy, cobalt-chromium alloy and stainless steel.

[0013] Furthermore, in the above-mentioned composite film structure, the outermost layers are Ta layer and Cu layer from inside to outside, the thickness of the Cu layer is 10-100 nm, and the thickness of the Ta layer is 150-250 nm.

[0014] Furthermore, in the above-mentioned composite film structure, the innermost layer is a Ti transition layer, and the thickness of the Ti transition layer is 50-300 nm.

[0015] Furthermore, in the composite film structure, the middle layer is -(Ta-Ti) n -, wherein the thickness of a single Ta layer is 100-220nm, and the thickness of a single Ti layer is 80-150nm.

[0016] Furthermore, the process conditions for the plasma treatment of medical materials are: vacuum degree 1-5Pa, cleaning time 5-60min, negative bias voltage 50-500V.

[0017] Furthermore, in the above-mentioned process of magnetron sputtering of medical materials, the process conditions are:

[0018] The vacuum degree is 0.2-1Pa, the negative bias voltage is 30-200V, the power is 200-500W, the target-sample distance is 50-120mm, the sputtering temperature is 20-150℃, and the sample is rotated 360° during DC magnetron sputtering at a speed of 8-12 r / min.

[0019] Furthermore, in the above-mentioned magnetron sputtering process of the medical material, the sputtering time is controlled according to the type of coating and the deposition rate, wherein the sputtering time of the Ti transition layer is 5-30 minutes, the sputtering time of the Ta layer is 10-30 minutes, and the sputtering time of the copper layer is 1-5 minutes.

[0020] In a second aspect, the present application provides a biomedical multifunctional coating, which is prepared by the above-mentioned preparation method.

[0021] Furthermore, the bonding strength of the multifunctional coating is above 44Mpa.

[0022] In summary, this application has the following beneficial effects:

[0023] The preparation method of the biomedical multifunctional coating provided in the present application first forms a micro-nano structure on the surface of the medical material through sandblasting, which helps to form a mechanical interlock between the coating and the medical material, increase the contact area between the coating and the medical material, and improve the bonding strength of the coating; at the same time, the coating formed by magnetron sputtering cannot change the micro-nano structure on the surface of the medical material, which helps cells to adhere, proliferate and differentiate, and further improves the bone integration ability.

[0024] After sandblasting, plasma treatment is used to generate a large number of argon ions to bombard the surface of the medical material, which can increase the surface active groups of the material, increase the surface energy, and enhance the bonding strength of the coating formed on the surface later.

[0025] During the magnetron sputtering process, a layer of Ti is first deposited as a transition layer, then a functional layer of Ta and Ti alternating is deposited, and finally a Ta and Cu layer is deposited. On the one hand, the Ti transition layer in this coating structure can form a strong bond with the medical material with a micro-nano structure on the surface, acting as a bridge and improving the bonding strength of Ta; the functional layer of Ta and Ti alternating can reduce the stress of the coating and improve the overall bonding strength of the coating. On the other hand, this coating structure can also retain the advantages of Ta, improve the bone integration ability of medical materials, and prevent bacterial infection around the implant through the bactericidal effect of copper.

[0026] The intermediate functional layer of the present application can form a Ta-Ti repeating coating unit with a specific structure and performance by alternately depositing Ta and Ti coatings. This structure not only has the excellent corrosion resistance, biocompatibility and wear resistance of the Ta coating, but also can optimize the overall performance of the coating by adjusting the ratio and distribution of Ta and Ti. At the same time, the alternating deposition of Ta and Ti coatings can form a dense composite structure, which effectively prevents the penetration of corrosive media and biological fluids, not only improves the corrosion resistance of the coating, but also reduces the dissolution and shedding of the coating in biological fluids, thereby enhancing the stability of the coating. And when the outermost Cu layer and Ta layer fail, the remaining coatings can still play a role, and the durability is also improved.

[0027] The preparation method of the present application is simple and easy to operate, and the plasma treatment can be completed by the coating equipment, avoiding process contamination. At the same time, by controlling the parameters such as argon gas pressure, deposition temperature, deposition time and power during the sputtering process, the tantalum coating is uniform and dense, and has strong bonding force (above 43Mpa). Both Ti and Ta in the coating are biocompatible, among which tantalum can promote bone integration, increase cell adhesion ability, promote cell growth, and accelerate healing time; Cu can reduce the risk of bacterial infection and further improve the success rate of implantation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a photo of a sample provided in Example 1 of the present invention;

[0029] Figure 2 is a SEM image of the tantalum coating on the surface of the sample of Example 1 of the present invention;

[0030] Figure 3 is a SEM image of a cross section of the tantalum coating in Example 1 of the present invention;

[0031] Figure 4 This is a test diagram of the coating bonding strength in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0033] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] Example 1

[0035] This embodiment provides a biomedical multifunctional coating, and the preparation method thereof includes:

[0036] (1) sandblasting the peek, then cleaning and drying it to obtain a peek with a surface micro-nano structure;

[0037] (2) The titanium target, tantalum target and copper target were installed on three targets in the magnetron sputtering instrument respectively. The target size was φ76.2 mm × 6 mm. The magnetron power supply used a DC power supply. The peek with surface micro-nano structure was placed in the magnetron sputtering instrument. The initial temperature was 18 °C. The vacuum was pumped to 3.5 × 10 -3 Pa, filled with argon.

[0038] (3) The peek was subjected to plasma treatment by bombarding the peek surface with argon ions. The vacuum degree was 2 Pa, the cleaning time was 10 min, and the negative bias voltage was 500 V.

[0039] (4) Magnetron sputtering was performed on the peek surface after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.5 Pa, coating time 15 min, negative bias voltage 100 V, power 350 W, target-sample spacing 80 mm, sputtering temperature 100 °C. The sample was rotated 360° during DC magnetron sputtering at a speed of 10 r / min.

[0040] (5) Magnetron sputtering coating is continued on the surface of the Ti transition layer of the peek material, and Ta layers and Ti layers are deposited alternately to form a peek-Ti-(Ta-Ti)- film layer. The actual photo is shown in Figure 1 As shown, Figure 2 and Figure 3 They are SEM images of the sample surface coating and SEM images of the coating cross section. It can be seen from the figures that the sample surface presents a micro-nano structure and has a coating of a certain thickness.

[0041] The process parameters for depositing the Ta layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 350 W, temperature 100 ° C, target sample spacing 80 mm, time 20 min;

[0042] The process parameters for depositing the Ti layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 350 W, temperature 100 ° C, target sample spacing 80 mm, and time 15 min.

[0043] (6) Magnetron sputtering coating is continued on the surface of the peek-Ti-(Ta-Ti)- film layer to deposit a Ta layer and a Cu layer in sequence, and finally a peek-Ti-(Ta-Ti)-Ta-Cu film layer structure is formed.

[0044] The process parameters for depositing the Ta layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 350 W, temperature 100 ° C, target sample spacing 80 mm, time 15 min;

[0045] The process parameters for depositing the Cu layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 400 W, temperature 100 ° C, target sample spacing 80 mm, and time 2 min.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 lies in step (5):

[0048] (5) Magnetron sputtering coating is continued on the surface of the Ti transition layer of the peek material to alternately deposit Ta layers and Ti layers to form a peek-Ti-(Ta-Ti)2- film layer, that is, the film layer structure of peek-Ti-(Ta-Ti)2-Ta-Cu is finally formed in this embodiment.

[0049] The process parameters for depositing the Ta layer and the Ti layer are the same as those in Example 1, except for the time: 17 min for depositing the Ta layer and 13 min for depositing the Ti layer.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 lies in step (5):

[0052] (5) Magnetron sputtering coating is continued on the surface of the Ti transition layer of the peek material to alternately deposit Ta layers and Ti layers to form a peek-Ti-(Ta-Ti)3- film layer, that is, the film layer structure of peek-Ti-(Ta-Ti)3-Ta-Cu is finally formed in this embodiment.

[0053] The process parameters for depositing the Ta layer and the Ti layer are the same as those in Example 1, except for the time: 12 minutes for depositing the Ta layer and 10 minutes for depositing the Ti layer.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 lies in step (6):

[0056] (6) Magnetron sputtering coating is continued on the surface of the peek-Ti-(Ta-Ti)- film layer to deposit a Ta layer and a Cu layer in sequence, and finally a peek-Ti-(Ta-Ti)-Ta-Cu film layer structure is formed.

[0057] The process parameters for depositing the Ta layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 350 W, temperature 100 ° C, target sample spacing 80 mm, time 20 min;

[0058] The process parameters for depositing the Cu layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 400 W, temperature 100 ° C, target sample spacing 80 mm, and time 5 min.

[0059] Example 5

[0060] The difference between this embodiment and embodiment 1 lies in the following steps:

[0061] (2) The titanium target, tantalum target and copper target were installed on three targets in the magnetron sputtering instrument respectively. The target size was φ76.2 mm × 6 mm. The magnetron power supply used a DC power supply. The peek with surface micro-nano structure was placed in the magnetron sputtering instrument. The initial temperature was 18 °C. The vacuum was pumped to 3.0 × 10 -3 Pa, filled with argon.

[0062] (3) The peek was subjected to plasma treatment by bombarding the peek surface with argon ions, the vacuum degree was 5 Pa, the cleaning time was 10 min, and the negative bias voltage was 500 V.

[0063] Example 6

[0064] The difference between this embodiment and embodiment 1 lies in the following steps:

[0065] Magnetron sputtering was performed on the peek surface after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.2 Pa, coating time 15 min, negative bias 200 V, power 500 W, target-sample spacing 120 mm, sputtering temperature 20 ° C. The sample was rotated 360° during DC magnetron sputtering at a speed of 12 r / min.

[0066] Example 7

[0067] (4) The difference between this embodiment and embodiment 1 lies in the following steps:

[0068] Magnetron sputtering was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 1 Pa, negative bias voltage 30 V, power 200 W, target sample spacing 50 mm, sputtering temperature 150 ° C, coating time 30 min. The sample was rotated 360° during DC magnetron sputtering at a speed of 8 r / min.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 1 is that in this comparative example, a Ti transition layer is not deposited, and a peek-Ta-Cu coating is directly formed. The specific method is as follows:

[0071] The tantalum target and the copper target were installed on different targets in the magnetron sputtering instrument. The target size was φ76.2mm×6mm, and the magnetron power supply used a DC power supply. The peek material after sandblasting was placed in the magnetron sputtering instrument. The initial temperature was 18℃ and the vacuum was evacuated to 3.5×10 -3 Pa, filled with argon. The plasma treatment process vacuum degree is 2Pa, the cleaning time is 10min, and the negative bias voltage is 500V. No Ti transition layer is deposited, and a single layer of Ta coating and Cu coating are deposited.

[0072] The process parameters for depositing the Ta layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 350 W, temperature 100 ° C, target sample spacing 80 mm, time 60 min;

[0073] The process parameters for depositing the Cu layer are: vacuum degree 0.6 Pa, negative bias voltage 100 V, power 400 W, temperature 100 ° C, target sample spacing 80 mm, and time 2 min.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that, after depositing the Ti transition layer, this comparative example directly deposits Ta and Cu layers to form a peek-Ti-Ta-Cu coating. The preparation method is basically the same as that of Example 1, except that the time for depositing the Ta layer is 50 minutes.

[0076] Comparative Example 3

[0077] The difference between this comparative example and Example 1 is that in this comparative example, no Ti transition layer is deposited, and Ta-Ti-Ta-Cu layers are deposited in sequence directly on the surface of the peek material after sandblasting, and the deposition method is consistent with that in Example 1.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the outermost layer of this comparative example is a Ta layer, and no Cu layer is deposited, that is, a peek-Ti-(Ta-Ti)-Ta coating, and the preparation method is consistent with that of Example 1.

[0080] Comparative Example 5

[0081] The difference between this comparative example and Example 1 is that, in this comparative example, no sandblasting was performed before depositing the Ti transition layer.

[0082] Performance Testing

[0083] (1) Coating thickness test standard: The sample film thickness test is carried out in accordance with "GB / T 31563-2015 Metal coating thickness measurement scanning electron microscope method".

[0084] (2) Coating adhesion test standard: The samples were tested in accordance with "YY / T 0988.11 Surgical Implant Coatings Part 11: Tensile Test Methods for Calcium Phosphate Coatings and Metal Coatings", where: Figure 4 This is a diagram illustrating the bonding strength test of the sample obtained in Example 1.

[0085] (3) Antibacterial ability: 40 μL of a concentration of about 10 7 100 / ml Staphylococcus aureus was dropped on the sample surface. After 6 hours of incubation, the surface was rinsed with PBS to remove bacteria that were not attached to the sample surface. The surface was fluorescently stained and observed with a laser confocal microscope. The fluorescence intensity of any 6 positions on each surface was counted and the inhibition rate (%) was calculated.

[0086] The results are shown in Table 1:

[0087] Table 1.

[0088] Membrane structure Ti transition layer thickness (nm) Total thickness of intermediate alternating functional layers (nm) Outer Ta layer thickness (nm) Outer Cu layer thickness (nm) Coating bonding strength (Mpa) Antibacterial rate (%) Example 1 Peek-Ti-Ta-Ti-Ta-Cu 150 350 200 60 48 95 Example 2 <![CDATA[Peek-Ti-(Ta-Ti)2-Ta-Cu]]> 150 600 200 60 61 94 Example 3 <![CDATA[Peek-Ti-(Ta-Ti)3-Ta-Cu]]> 150 660 200 60 65 96 Comparative Example 1 Peek-Ta-Cu / / 700 60 17 95 Comparative Example 2 Peek-Ti-Ta-Cu 150 / 600 60 31 94 Comparative Example 3 Peek-Ta-Ti-Ta-Cu / 350 200 60 29 95 Comparative Example 4 Peek-Ti-Ta-Ti-Ta 150 350 200 / 47 56 Comparative Example 5 Peek-Ti-Ta-Ti-Ta-Cu 150 350 200 60 34 94

[0089] It can be seen from Table 1 that:

[0090] As can be seen from Examples 1-3 and Comparative Example 2, the medical material with a specific film structure obtained in the present application has a high coating bonding strength and a strong antibacterial ability. n-When the number of repeated layers n is 2 and 3, the coating bonding strength increases significantly. This indicates that the alternating deposition of Ta and Ti coatings can form Ta-Ti repeated coating units with specific structures and properties, which helps to reduce coating stress and improve coating bonding strength.

[0091] It can be seen from Example 1 and Comparative Examples 1-3 that when the film structure does not contain a Ti transition layer, since the Ta film is directly plated on the surface of the peek material after sandblasting, the coating stress is too high and the bonding strength is weak.

[0092] It can be seen from Example 1 and Comparative Example 4 that plating a Cu layer on the outermost layer of the film layer can improve the antibacterial property of the medical material.

[0093] It can be seen from Example 1 and Comparative Example 5 that Comparative Example 5 was not subjected to sandblasting before coating, and the film surface was smooth. Under the same film conditions, the coating bonding strength of Comparative Example 5 was weak.

[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a biomedical multifunctional coating, characterized in that: It includes: Performing sandblasting on medical materials to obtain medical materials with surface micro-nano structures; The titanium target, the tantalum target and the copper target are respectively mounted on three targets in a magnetron sputtering apparatus, the medical material is placed in the magnetron sputtering apparatus, evacuated and filled with argon gas, the medical material is subjected to plasma treatment, and the surface of the medical material is bombarded with argon ions; Performing magnetron sputtering coating on the surface of the medical material after plasma treatment to deposit a Ti transition layer; Magnetron sputtering coating is continued on the surface of the transition layer of the medical material to alternately deposit Ta layers and Ti layers to form -(Ta-Ti) n -functional layer, where n=1~3; A Ta layer is deposited on the surface of the functional layer of the medical material, and then a Cu layer is deposited on the surface of the Ta layer, and finally a -Ti-(Ta-Ti) is formed on the surface of the medical material. n -Ta-Cu composite film structure.

2. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: The medical material includes any one of PEEK material, titanium alloy, cobalt-chromium alloy and stainless steel.

3. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: In the composite film structure, the outermost layers are Ta layer and Cu layer from inside to outside, the thickness of the Cu layer is 10-100 nm, and the thickness of the Ta layer is 150-250 nm.

4. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: In the composite film structure, the innermost layer is a Ti transition layer, and the thickness of the Ti transition layer is 50-300 nm.

5. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: In the composite film structure, the middle layer is -(Ta-Ti) n -, wherein the thickness of a single Ta layer is 100-220nm, and the thickness of a single Ti layer is 80-150nm.

6. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: The process conditions for plasma treatment of the medical material are: vacuum degree 1-5Pa, cleaning time 5-60min, negative bias voltage 50-500V.

7. The method for preparing the biomedical multifunctional coating according to claim 1, characterized in that: During the magnetron sputtering process of the medical material, the process conditions are: The vacuum degree is 0.2-1Pa, the negative bias voltage is 30-200V, the power is 200-500W, the target-sample distance is 50-120mm, the sputtering temperature is 20-150℃, and the sample is rotated 360° during DC magnetron sputtering at a speed of 8-12 r / min.

8. The method for preparing the biomedical multifunctional coating according to claim 7, characterized in that: During the magnetron sputtering of the medical material, the sputtering time is controlled according to the type of coating and the deposition rate, wherein the sputtering time of the Ti transition layer is 5-30 minutes, the sputtering time of the Ta layer is 10-30 minutes, and the sputtering time of the copper layer is 1-5 minutes.

9. A biomedical multifunctional coating, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. The biomedical multifunctional coating according to claim 9, characterized in that: The bonding strength of the multifunctional coating is above 44 MPa.

Citation Information

Patent Citations

  • Composite coating having antibacterial performance and biocompatibility as well as preparation method and application of composite coating

    CN108904893A

  • Preparation method of medical coating on surface of titanium alloy

    CN111074220A